Intracellular and Extracellular Metabolites from the Cyanobacterium Chlorogloeopsis fritschii, PCC 6912, During 48 Hours of UV-B Exposure - Carole Llewellyn (Metabolites, 2019)
Cyanobacteria have many defence strategies to overcome harmful ultraviolet (UV) stress including the production of secondary metabolites. Metabolomics can be used to investigate this altered metabolism via targeted and untargeted techniques. In this study we assessed the changes in the intra- and extracellular low molecular weight metabolite levels of Chlorogloeopsis fritschii (C. fritschii) during 48 h of photosynthetically active radiation (PAR) supplemented with UV-B (15 µmol m−2 s−1 of PAR plus 3 µmol m−2 s−1 of UV-B) and intracellular levels during 48 h of PAR only (15 µmol m−2 s−1) with sampling points at 0, 2, 6, 12, 24 and 48 h. Gas chromatography–mass spectrometry (GC–MS) was used as a metabolite profiling tool to investigate the global changes in metabolite levels. The UV-B time series experiment showed an overall significant reduction in intracellular metabolites involved with carbon and nitrogen metabolism such as the amino acids tyrosine and phenylalanine which have a role in secondary metabolite production. Significant accumulation of proline was observed with a potential role in stress mitigation as seen in other photosynthetic organisms. 12 commonly identified metabolites were measured in both UV-B exposed (PAR + UV-B) and PAR only experiments with differences in significance observed. Extracellular metabolites (PAR + UV-B) showed accumulation of sugars as seen in other cyanobacterial species as a stress response to UV-B. In conclusion, a snapshot of the metabolome of C. fritschii was measured. Little work has been undertaken on C. fritschii, a novel candidate for use in industrial biotechnology, with, to our knowledge, no previous literature on combined intra- and extracellular analysis during a UV-B treatment time-series. This study is important to build on experimental data already available for cyanobacteria and other photosynthetic organisms exposed to UV-B